2015
DOI: 10.1007/s11306-015-0808-5
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the 1H NMR data of serum, urine and exhaled breath condensate in order to discriminate chronic obstructive pulmonary disease and obstructive sleep apnea syndrome

Abstract: Chronic obstructive pulmonary disease, COPD, affects the condition of the entire human organism and causes multiple comorbidities. Pathological lung changes lead to quantitative changes in the composition of the metabolites in different body fluids. The obstructive sleep apnea syndrome, OSAS, occurs in conjunction with chronic obstructive pulmonary disease in about 10–20 % of individuals who have COPD. Both conditions share the same comorbidities and this makes differentiating them difficult. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Metabolomic approaches have been applied in the study of OSA, whereby they can be categorized into two types of studies, including (1) metabolomic studies of exhaled breath [ 38 , 39 , 40 ], and (2) studies of the blood and/or urine metabolome [ 41 , 42 , 43 , 44 ].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolomic approaches have been applied in the study of OSA, whereby they can be categorized into two types of studies, including (1) metabolomic studies of exhaled breath [ 38 , 39 , 40 ], and (2) studies of the blood and/or urine metabolome [ 41 , 42 , 43 , 44 ].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…More specifically, aromatic hydrocarbons (phenylacetic acid, ethylbenzene, toluene and p-xylene), saturated hydrocarbons (hexane, octane, heptane, nonane and decane), acetone and isoprene were elevated, which have been suggested as potential biomarkers. However, studies have shown that changes in the metabolomics profile of exhaled breath might not be specific enough to differentiate between patients with different respiratory disorders, such as chronic obstructive pulmonary disease and OSA [ 42 ]. Therefore, the second group of studies (studies of the blood and/or urine metabolome) might provide a more specific characterization of OSA.…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…To date, a limited number of small-sample-size metabolomics studies have been performed to explore metabolomics profiling and the underlying mechanisms in OSA 13 14 15 . Thus, we utilized a combination of ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) and gas chromatography coupled with time-of-flight mass spectrometry (GC-TOF-MS) to investigate: the metabolic changes occurring during the development of OSA, the mechanistic pathways involved in OSA, and candidate metabolite markers useful for diagnosing OSA.…”
mentioning
confidence: 99%
“…Accordingly, in an animal model, NMR‐based profiling studies on different biological matrix (e.g. serum, urine, and others) consistently detected distinct biomarker signatures with respect to controls and in patients affected by COPD and OSA, specific biomarkers were identified in distinct matrices …”
mentioning
confidence: 91%